Helping Parliaments to Help the Poor - Stapenhurst, Frederick C. (World Bank, Washington, DC, 2012)
One of the key features of the PRSP process is that, while government led, there should be broad consultations within countries and wide participation by civil society, to ensure "country ownership." The involvement of Parliaments could be even more pervasive, however, given that, in many countries, parliaments have become key pressures for government reform, aiming to see that governments work more effectively, efficiently, and openly. How this was done depended on circumstances and opportunities to achieve positive change. The strengthening of parliamentary committee capacity seems to offer the most promise, but significant improvements in performance which committees work to achieve are often necessary to have such an impact.